Assessment of tele-expertise among elderly subjects in retirement homes - Sparsa, A; Doffoel-Hantz, V; Bonnetblanc, J-M (Annales de dermatologie et de vénéréologie, 2013)
Chronic wounds (leg ulcers, pressure ulcers, diabetic foot ulcers, etc.) constitute a real public health problem and engender high economic and human costs. Due to the declining physical and mental conditions of our elderly subjects and their rural environment, we created a computer program to assist with chronic wound management in elderly subjects living in retirement homes and to reduce the amount of ambulance transportation. Each participating establishment was provided with a digital camera and its own secure e-mail address in order to allow photographs to be sent anonymously. Patients with chronic wounds entailing treatment difficulties were included. Details were recorded of the number of tele-expertise consultations given, the chronic wound type, the number of hospitalizations or medical consultations, and the number of ambulance trips avoided. The project was evaluated at 1 year. Of the 40 establishments invited to take part, 22 agreed to do so but only the first 10 respondents were accepted for participation in the pilot feasibility study. Funding ("Health and social prize" provided by the Haute-Vienne region Social Security Office - CPAM) was used to purchase the cameras. Beginning on 15 April 2010, 10 establishments for the elderly sent photographs of 34 patients presenting 26 chronic wounds and tele-expertise was provided for 10 pressure ulcers, two diabetic feet and 14 leg ulcers. Over a two-year period, this program helped avoid 20 trips for patients and enabled rapid hospitalization of nine patients by the university hospital by optimizing chronic wound management for patients residing in establishments for the elderly.